Efficacy of desensitizing agents on postoperative sensitivity following an in-office vital tooth bleaching: A randomized controlled clinical trial - Nanjundasetty, Jyothi; Ashrafulla, Mohammed (Journal of conservative dentistry, 2016)
Aim: To assess and compare the incidence and intensity of experienced after an in-office vital tooth bleaching in case of dental fluorosis using two different types of desensitizing agents, at different time periods. Materials and Methods: Sixty-nine subjects with mild-to-moderate fluorosis were randomly divided into three groups of 23 each. Group I - control group (placebo), group II-potassium nitrate 5% and sodium monofluorophosphate 0.7% (Sensodent KF), and group III-Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP) (Tooth Mousse). In-office vital tooth bleaching was done using 35% hydrogen peroxide liquid (Pola office) in two sessions. Desensitizing agent was applied for 10 min after each session. Postoperative sensitivity was recorded after 24 h and 7 days. The statistical analysis was done using chi-square test, analysis of variance (ANOVA), and post hoc Tukey′s test. Results: The experimental groups showed significantly less incidence and intensity of sensitivity compared to control group, whereas there was no difference between them. Conclusion: The desensitizing agents used in the study show effective reduction after an in-office vital tooth bleaching.